Identification of multi-level toxicity of liquid crystal display wastewater toward Daphnia magna and Moina macrocopa - Kim, Sae-Bom; Kim, Woong-Ki; Chounlamany, Vanseng; Seo, Jaehwan; Yoo, Jisu; Jo, Hun-Je; Jung, Jinho (ELSEVIER SCIENCE BV, 2012)
Toxicity-based regulations of industrial effluent have been adopted to complement the conventional discharge limits based on chemical analyses. In this study, multi-level toxicity including acute toxicity, feeding rate inhibition and oxidative stress of effluent from a liquid crystal display (LCD) wastewater treatment plant (WWTP) to Daphnia magna (reference species) and Moina macrocopa (native species) were periodically monitored from April 2010 to April 2011. Raw wastewater was acutely toxic to both D. magna and M. macrocopa, but the toxicity reached less than 1 TU in the final effluent (FE) as treatment proceeded. Although acute toxicity was not observed in the FE, the feeding rate of daphnids was significantly inhibited. Additionally, the antioxidant enzyme activity of catalase, superoxide dismutase and glutathione peroxidase (GPx) in D. magna increased significantly when compared to the control, while only GPx activity was increased significantly in M. macrocopa (p < 0.05). A toxicity identification evaluation using D. magna showed that Cu was the key toxicant in the FE, which was not effectively removed by the coagulation/flocculation process in the LCD WWTP. In addition, AI originating from the coagulant seemed to increase toxicity of the FE. (c) 2012 Elsevier B.V. All rights reserved.